TANTANGAN GERAKAN PEREMPUAN BERBASIS KOMUNITAS LOKAL - Yuhelna yuhelna; Isnaini isnaini; Yanti Sri Wahyuni (Universitas Islam Negeri Imam Bonjol Padang, 2018)
In Minangkabau community, ulayat land known as heritage is a land dominated by ninik mamak and ownership by women, actually ulayat always dominated by ninik mamak. This study aims to describe the challenge in the women's struggle against ulayat land by men in the Gunung Sarik Distrik, Padang. The qualitatif methode was done by using in-depth interview and focus group discussion with informant taken by purposive sampling. Women who are members of Gunung Sarik Saiyo Cooperative meet the obstacles in the struggle that is the first, the social system that is not supported. Second, get challenges from other people in community. Thirdly, the streotype of society is not good for women who often do activities outside the home in Gunung Sarik Village.